Assessing agricultural losses of 2014/2015 flood disaster in Kelantan, Malaysia - Jega, Abdussalam Adamu; Man, Norsida; Abd Latiff, Ismail; Wong, Kelly Kai Seng (Premier Publishers, 2018)
Floods account for a significant socio-economic loss against all other natural disasters occurring in most part of the world in recent decades, especially to small farming communities living along coastal and low-lying areas. Hence, flood loss assessment which has become an important segment in decision making processes towards flood risk management needs to be given adequate attention by the policy makers and/or researchers. This paper therefore, aimed at describing and examining the extent of agricultural losses of 2014/2015 flood disaster in Kelantan, Malaysia. Data were gathered from 344 smallholder farmers using multi-stage sampling technique and analyzed through the use of descriptive (using bar charts) and Paired sample t-test. Findings of the study revealed that, agricultural losses incurred by farmers were significant at 5% level of significance for almost all the reported crops, livestock and agricultural assets. The implication of this study would give an insight to the policy makers in facilitating cost-effective integrated flood management to avoid future losses. In addition, while promising a baseline data it would further give an insight to the academicians in employing advanced methods of analysis while undertaking post disaster damage, loss and needs assessment of flood and/or other natural disasters in the future.